DETERMINING STORAGE POTENTIAL OF NATURALLY AGED SEEDS OF PADDY VARIETIES - CH. DAMODAR RAJU, S.U.M.S. SAMPATH, K. JHANSI RANI*, P. SUJATHA, M. SREEDHAR and (The Journal of Research, PJTSAU, 2019)
Even though rice seed is a good storer, loss in seed quality during storage frequently takes place especially in humid tropical and subtropical areas. Seed deterioration is a natural process which is expressed as loss of quality, viability and vigour during ageing or adverse environmental conditions. The rate of deterioration is however influenced by seed moisture content and temperature of the storage. Many physical and biochemical manifestations of seed deterioration have been reported by Jatoi et al. (2004). Most widely accepted single criteria of seed deterioration is reduced germination. In order to preserve the planting value of seed, information on storage potential of important varieties is essential. Manipulation of storage environment and usage of suitable packaging material has to be recommended for certain varieties having relatively poor storability. As information available regarding the storage response and relative storability of cereal crops in general and relative storability of different paddy varieties in particular is meagre, present study was undertaken to estimate seed storage potential and relative storability of naturally aged seeds of seven paddy varieties viz., Tellahamsa, RNR-15048, WGL- 347, KNM-118, JGL-11118, JGL-11470 and JGL-18047 of which six are recently released by Professor Jayashankar Telangana State Agricultural University except Tellahamsa.